The impact of climate shocks exposure to depressive and suicidal ideations among female population in Kilifi rural areas, KenyaResearch in context - Cyprian M. Mostert; Manasi Kumar; Anthony Ngugi; Jasmit Shah; Edna Bosire; Andrew Aballa; Lukoye Atwoli; Zul Merali (EBioMedicine)
Summary: Background: Few African studies have established links between climate shocks and mental health outcomes. This study examines the impact of climate change-related shocks on depressive symptoms and suicidal thoughts in a group of 14,801 female participants dependent on the informal agricultural sector. Methods: Women living in informal settlements without running water or flushing toilets were classified as the treatment group, while rural women with basic amenities served as the control group. We applied a two-stage least-squares model to assess the effects of climate shocks—reduced rainfall, heat waves, and drought—on depression and suicidal ideation. Findings: Climate shocks contribute towards a 10.8% [95% CI: 2.3%–17.7%] increase in depressive symptoms in the women from the informal settlement group versus the women from rural households. These increases in depressive symptoms have significant negative spillover effects on suicidal ideation in the woman living in informal settlements. Less rain was associated with 28.7% [95% CI: 22.5%–34.5%] higher suicidal ideation in the woman living in informal settlements. Heat waves increased suicidal ideation by 14.9% [95% CI: 7.6%–20.7%]. Drought caused a 36.7% [95% CI: 29.4%–41.1%] increase in suicidal ideation. The accumulative effects of climate change shocks and high food prices increased suicidal ideation by 48.3% [95% CI: 35.2%–54.9%]. Interpretation: Climate change shocks worsen depression and consequently drive suicidal thoughts in women from informal settlements with varying intensity. Kenyan policymakers may need to prioritize the provision of mental health services in the aftermath of climate change-related shocks. Funding: This study was supported by the Canadian philanthropic foundation called the Waverley House. This funding is used to support all research projects of the Brain and Mind Institute, Aga Khan University.